Integrated metabolomic and metagenomic strategies shed light on interactions among planting environments, rhizosphere microbiota, and metabolites of tobacco in Yunnan, China - Liao, Rentao; Liu, Zhengjie; Dongchen, Wenhua; Deng, Xiaopeng; Ma, Erdeng; Manzoor, Nazer; Lin, Chun; Zhou, Shaosong; Tong, Wenjie; Zhou, Min; Li, Junying; Mao, Zichao (Frontiers in Microbiology, 2024)
Changes in climatic factors and rhizosphere microbiota led plants to adjust metabolic strategies for survival under adverse environmental conditions. Changed plant metabolites can meditate crop growth & development and interact with rhizosphere microbiota of plant rhizosphere. To understand the interactions among environmental factors, rhizosphere microbiota and metabolites of tobacco, a study was conducted by using integrated metagenomic and metabolomic strategies at 4 typical representative tobacco planting sites of Yunnan, China. The results showed that the agronomical and biochemical traits were significantly affected by temperature, precipitation (PREP), soil pH and altitude. Correlation analyses revealed a significant positive correlation of temperature with length, width and area of the leaf, while PREP correlated with plant height and effective leaf numbers. Furthermore, total sugar and reducing sugar contents of baked leaves were significantly higher, while the total nitrogen and total alkaloids were lower in leaves of tobacco at site with low PREP. A total, 770 metabolites were detected with the highest number of different abundant metabolites (DMs) at Chuxiong (CX) with low PREP as compared to the other 3 sites, in which secondary metabolites were more abundant in both leaves and roots of tobacco. A total of 8,479 species, belonging to 2,094 genera with 420 individual bins (including 13 higher quality bins) harboring 851,209 CDSs were detected. The phyla levels of microorganisms such as Euryarchaeota, Myxococcota and Deinococcota were significantly enriched at CX site, while Pseudomonadota was enriched at the high temperature site with good PREP. The correlation analyses showed that the metabolic compounds in low PREP site samples were positively correlated with Diaminobutyricimonas, Nissabacter, Alloactinosynnema and Catellatospora, while negatively correlated with Amniculibacterium, Nordella, Noviherbaspirillum and Limnobacter suggesting the recruitment of Diaminobutyricimonas, Nissabacter, Alloactinosynnema and Catellatospora in rhizosphere to induce the production and accumulation of secondary metabolites (SMs) (e.g., nitrogen compounds, terpenoids, and phenolics) to increase drought tolerance with unknown-mechanism. The results of this study may promote the production and application of microbial fertilizers and agents such as Diaminobutyricimonas and Alloactinosynnema to assemble synthetic microbiota community or using their gene resources for better cultivation of tobacco as well as other crops in drought environments.